Writing the Chilean language and literature curriculum: experiences from the construction process - Soto, Guillermo; Concha, Soledad; Guajardo, Javiera (Lenguas Modernas, 2023)
This paper explores the experience of constructing the current 1st to 10th grade Language curriculum in Chile. A central underlying assumption is that the curricular text not only corresponds to an institutional authorship, but is also a discursive process in which curriculum developers and other intervening voices put into play their beliefs, ideologies and knowledge. Using a narrative approach, memories and reflections on this process were recovered through four dialogical interviews with the curriculum team. The results reveal tensions in the curricular discourse regarding the sources and contents of knowledge, as well as the conceptualization of its recipients. A discussion is offered on how the disciplinary and didactic dimensions of language and literature are integrated in the discourse and in the curricular text with definitions of the type of person and the type of society to which the curricular policy is oriented.